Pengaruh Total Aset, Utang Jangka Pendek, dan Utang Jangka Panjang Terhadap Laba Usaha Pada Industri Rokok Di Bursa Efek Indonesia Periode 2013-2018 - Eltrina Debora Hutabarat (Science of Management and Students Research Journal (SMS), 2020)
This study aims to determine how the influence of Total Assets, Short-term Debt and Long-Term Debt to Operating Profits both partially and simultaneously. This study took the object of the cigarette industry listed on the Indonesia Stock Exchange for the period 2013-2018. The sample selection uses a purposive sampling method. The analytical method used is quantitative descriptive analysis method. The analytical tool in this study is the classic assumption test, multiple regression analysis with panel data, and hypothesis testing. The research was conducted in the cigarette industry consisting of Gudang Garam, Tbk, PT Wismilak Inti Makmur Tbk, and PT. HM Sampoerna Tbk. From the calculation using SPSS 21, the results of the study show Total Assets (X1), Short-term Debt (X2) and Long-Term Debt (X3) that affect Operating Income (Y) as seen in table F (31,893> 2.14). partial, inventory has a significant negative effect on Operating Income. The results showed that the data used in this study fulfilled the classical assumptions which included: data were normally distributed, there were no symptoms of multicollinearity, no symptoms of heteroscedasticity, and autocorrelation did not occur. Simultaneously there is a significant effect on Operating Profit, partially all Total Asset, Short-Term Debt and Long-Term Debt variables affect Y, while firm size does not affect Y.